The Open2-Innova8ion Tool - A Software Tool for Rating Organisational Innovation Performance - Caird, Sally P.; Hallett, Stephen H.; Potter, Stephen (Elsevier Science B.V., Amsterdam., 2013)
The Open2-Innova8ion Tool is an interactive, multi-media, web-based software tool for rating organisational innovation performance. This tool was designed for organisations to use as an adaptation of the European Commission's work on developing empirical measures of national innovation performance with the Summary Innovation Index (SII). It is designed for users with experience of employment in an organisation, from senior managers to all types of employees, with an interest in rating the innovation performance of their organisation. The Tool is quick and intuitive to use, and provides textual feedback, together with graphic ratings using Google meters. Feedback is based on user perceptions of organisational indicators of Innovation Enablers, Activities, and Outputs to provide an overall rating of innovation performance; this can be compared with a self-rating of innovativeness to allow some interpretation of the congruence between the user and their organisation. This prototype Tool was trialled and evaluated during a workshop on low carbon vehicle innovation, with participants (innovators) representing organisations from the surface transport industry as part of the U-STIR programme with EU Framework 7 funding. This publically available web-tool has applications to education, training, and research http://design.open.ac.uk/itool/.
Keywords: innovation rating tool; educational software tool; organisational innovation; innovation assessment; innovation indicators; tool design; low carbon transport